2020
DOI: 10.1016/j.jjcc.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Public location and survival from out-of-hospital cardiac arrest in the public-access defibrillation era in Japan

Abstract: A B S T R A C TBackground: The use of public-access automated external defibrillators (AEDs) has become common in Japan. To provide a strategy for appropriate public-access AED deployment, we assessed public-access defibrillation (PAD) by laypersons and the outcomes following out-of-hospital cardiac arrest (OHCA) among adult patients by location of arrest. Methods: From a nationwide, prospective, population-based registry of patients after OHCA in Japan, we enrolled adult patients with bystander-witnessed OHCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Approximately 30% of OHCAs in Japan occur in public places, and many of these are expected to survive with bystander intervention. 2 In Japan, citizen cardiopulmonary resuscitation (CPR) has been promoted since 1993, and the bystander cardiopulmonary resuscitation rate (BCPR) improved 56.6% by 2018. 3 Over 40,000 automated external defibrillators (AEDs) have been installed throughout Tokyo since the Public Access Defibrillation (PAD) program was introduced in 2004, 4 but the PAD implementation rate remains near 13%.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of OHCAs in Japan occur in public places, and many of these are expected to survive with bystander intervention. 2 In Japan, citizen cardiopulmonary resuscitation (CPR) has been promoted since 1993, and the bystander cardiopulmonary resuscitation rate (BCPR) improved 56.6% by 2018. 3 Over 40,000 automated external defibrillators (AEDs) have been installed throughout Tokyo since the Public Access Defibrillation (PAD) program was introduced in 2004, 4 but the PAD implementation rate remains near 13%.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that family members could be at any OHCA location other than home. 11) Regarding the primary outcomes, group B had significantly less frequent bystander-initiated CPR and AED pad application compared with group A. On the other hand, the secondary outcomes of ROSC before EMS arrival and one-month survival rate were better in group B compared with group A.…”
Section: Discussionmentioning
confidence: 81%
“…This retrospective observational study demonstrated that autonomous bystander-initiated CPR and public access defibrillation for OHCA patients were significantly less frequent, compared with non autonomous CPR, even after adjusting for age, sex, and witness status. Although the frequency of AED use by citizens has been reported to differ according to specific public location, 11,12) increasing use of bystander defibrillation in public locations has been reported. 6) However, previous reports did not discriminate autonomous CPR (good Samaritans) from non autonomous CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, community ties, regional activation, CPR education systems, emergency request systems, and other community medical initiatives are issues to be addressed 7) .…”
Section: Rationale and Design Of The Kento Heart Safe City Project: A First-aid System Using An Emergency Alarm Button (Sos Button)mentioning
confidence: 99%